Let f ( x ) = 1 + x 2 x .
Define f ( n ) ( x ) = f ( f ( ⋯ f ( x ) ) ) , that is f composed with itself n times.
Find f ( 9 9 ) ( 1 ) .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Nicely done! Although you should be consistent with your notation. You should have f ( n ) ( x ) in all your working (note the brackets).
Nice solution
My method is Similar to Ahmed's, but I will creating a general formula for f ( 9 9 ) ( x ) : f ( f ( x ) ) = 1 + 1 + x 2 x 2 1 + x 2 x × 1 + x 2 1 + x 2 = 1 + 2 x 2 x . Now I want to prove by induction that: f n ( x ) = 1 + n x 2 x . . . . f n + 1 ( x ) = 1 + n 1 + x 2 x 2 1 + x 2 x × 1 + x 2 1 + x 2 = 1 + x 2 + n x 2 x = 1 + ( n + 1 ) x 2 x a s r e q u i r e d ∴ f 9 9 ( 1 ) = 1 0 0 1 = 0 . 1 ( o r − 0 . 1 )
Almost correct. You should be consistent with your notations. You used f ( 9 9 ) ( x ) and f 9 9 ( x ) . The square root function output the non-negative value only, so f ( 9 9 ) ( 1 ) > 0 only.
Problem Loading...
Note Loading...
Set Loading...
We see that f ( 1 ) = 2 1 , f 2 ( 1 ) = 3 1 , , f 3 ( 1 ) = 4 1 , f 4 ( 1 ) = 5 1 and so on.
So it seems that f n ( 1 ) = n + 1 1 In order to see if this holds for all positive integral values of n , we will use induction. Our base case is n = 1 , and our equation holds. Now we assume that f n ( 1 ) = n + 1 1 holds for n , so now we try for n + 1 .
f n + 1 ( 1 ) = f ( f n ( 1 ) ) = 1 + ( f n ( 1 ) ) 2 f n ( 1 ) = 1 + ( n + 1 1 ) 2 n + 1 1 = 1 + n + 1 1 n + 1 1 = n + 1 n + 2 n + 1 1 = n + 1 n + 2 n + 1 1 = n + 2 1
Hence the assumption is true.
Now we just plug in n = 9 9 . f 9 9 ( 1 ) = 1 0 1 .